2014
DOI: 10.1159/000360904
|View full text |Cite
|
Sign up to set email alerts
|

Intense Exercise Causing Central Retinal Vein Occlusion in a Young Patient: Case Report and Review of the Literature

Abstract: We report a 19-year-old patient who developed a central retinal vein occlusion (CRVO) with significant macular edema and visual impairment following intense exercise and dehydration. The patient was treated with 3 intravitreal bevacizumab injections with complete resolution. A review of the literature on the cause and treatment for CRVO in young patients was performed, focusing on the role of intense exercise and dehydration as a rare pathogenesis mechanism of CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, in such patients, there is no consensus on which should be used, notably because of the small number of subjects and lack of randomized trials. Moisseiev et al and Jacobs et al showed improvement in visual acuity and resolution of macular edema, in similarly reported cases with the use of bevacizumab [ 7 , 9 ]. In our patient, we decided to use ranibizumab, which produced an excellent result.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in such patients, there is no consensus on which should be used, notably because of the small number of subjects and lack of randomized trials. Moisseiev et al and Jacobs et al showed improvement in visual acuity and resolution of macular edema, in similarly reported cases with the use of bevacizumab [ 7 , 9 ]. In our patient, we decided to use ranibizumab, which produced an excellent result.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, hypercoagulability states, vasculitis, medications, trauma, hyperlipidemia, hyperhomocysteinemia, and other unusual causes should be ruled out. Intense exercise may be associated with CRVO in young patients, with no other comorbidities [ 4 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal vascular occlusions following intense exercise and dehydration are a rare occurrence. In the literature, there are few reports of isolated CRVO caused by intense exercise [ 2 - 3 ]. Our relatively young patient developed combined CRVO and BRAO soon after completing a half marathon.…”
Section: Discussionmentioning
confidence: 99%
“…These two types of ocular vascular obstructions are typically associated with similar systemic conditions, such as cardiovascular atherosclerotic disease, arterial hypertension, and diabetes mellitus. In addition, certain uveitic and vasculitic conditions, lymphoproliferative disorders, medications, trauma, as well as hypercoagulable syndromes, such as antiphospholipid syndrome and homocysteinemia, can lead to these occlusive events [ 2 ]. There have been few case reports in the literature of vascular occlusions in young patients following intense dehydration due to either fasting or intense exercise [ 2 - 4 ].…”
Section: Introductionmentioning
confidence: 99%